WOMEN IN AGRICULTURE: CHALLENGES AND OPPORTUNITIES IN KARNATAKA - Balaji, Brinda; Khandimath, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women play a fundamental role in Karnataka’s agricultural sector, contributing significantly to various farming activities such as seed selection, planting, weeding, harvesting, and post-harvest processing. However, their contributions remain largely unrecognized due to structural and systemic barriers. A key challenge faced by women in agriculture is the lack of land ownership, which restricts their access to credit, agricultural subsidies, and government support programs. Traditionally, land inheritance practices favor men, leaving women dependent on male family members for agricultural resources and decision-making power. This economic dependence often prevents them from participating in agricultural policymaking and restricts their ability to modernize their farming techniques. Post-liberalization agricultural policies have attempted to address some of these disparities through initiatives such as Farmer Producer Organizations (FPOs), self-help groups (SHGs), and microcredit schemes. These programs have empowered women by providing financial resources and encouraging collective farming practices. However, regional disparities persist, with women in South Karnataka benefiting more from these initiatives due to better access to markets and credit facilities. In contrast, women in North Karnataka continue to struggle against entrenched patriarchal norms that confine them to non-wage labor on family farms, depriving them of financial autonomy. This article explores the various socio-economic and policy-driven challenges faced by women in Karnataka’s agricultural sector. It highlights the existing government initiatives aimed at bridging the gender gap and evaluates their effectiveness. Additionally, the study emphasizes the need for more inclusive agricultural policies that recognize women’s contributions, promote land ownership rights, improve access to financial services, and ensure equitable decision-making power in the agricultural sector. Addressing these issues will not only empower women but also contribute to overall rural development and food security in Karnataka.